Fabrication and microstructural characterization of MgO composites for biomedical applications using the bottom pour stir casting process. (2023) - Sundaram, Jayavelu; Rajkumar, C.; Balaji, D.; Vijay Albert William, M.; Karthick, K.; SaralaRubi, C.
Abstract: Magnesium oxide (MgO) has caught the attention of researchers to use it as a replacement for common 316L stainless steel in the biomedical field since it is a biocompatible and biodegradable metal. MgO and Tricalcium Phosphate (TCP) were mixed in various combinations to make MgO composites using the bottom pour stir casting method. Three samples were fabricated at 960 °C and extruded as rods: sample1 was a MgO alloy, sample2 was a MgO with 5 wt% of TCP, and sample3 was a MgO with 10 wt% of TCP. For Scanning Electron Microscope, hardness testing, and microstructure analysis, rods were chopped into billets, and the results were compared. Of three composites, Sample3 of (90 wt% of MgO + 10 wt% of TCP) shows better results than other samples and alloy. Magnesium composites containing 10 % TCP had a better microstructure, and a higher hardness value, indicating that they might be used as biodegradable materials in the biomedical field.